Stability enhancement of an islanded distribution network via boundary detection and load shedding - Adrian Stuart Tang (2023)
Distributed generation (DG) based on renewable energy sources (RES) was introduced into power systems to reduce the dependence on fossil fuel for electricity generation. The increased RES penetration in distribution systems has caused new issues to emerge, of which one is the islanding phenomenon. Islanding can be a solution to maintaining the continuity of supply in a distribution system if proper control and operation were established. In this thesis, a boundary detection method, which is derived from graph theory, was developed to detect islanding and to determine the newly formed electrical network post-islanding. A remote islanding detection method was established by combining the boundary detection method with current measurements across the distribution network. To maintain the stability of the distribution network postislanding, a system stabilization scheme was proposed. The proposed system stabilization scheme aims to maintain the balance between generation and load demand in the distribution network post-islanding. Hence, a dynamic voltage collapse prediction index was introduced to detect the weakest bus in each islanded network. Next, with the aid of the boundary detection method, load shedding was performed on the weakest bus until the distribution network becomes stable. The proposed islanding detection method and system stabilization scheme were simulated with PSCAD/EMTDC and MATLAB software. A practical 37-bus distribution network operating at 11 kV was modeled as the test bed. Two 1 MVA DG units with an AVR and a governor were also modeled to study the islanding phenomenon, as well as to validate the capability of the boundary detection method in identifying multiple islanded networks. The developed boundary detection method successfully detected the topology of the newly formed distribution networks after islanding occurred. It is proven to be capable of detecting radial and mesh topology, while keeping track of the changes that occurs in the network. Moreover, the combination of the proposed dynamic voltage collapse prediction index and the load shedding scheme was proven to be effective in stabilizing the islanded networks. With load shedding taking place in multiple steps, as shown in the PSCAD/EMTDC simulation results, the amount of load to be shed is minimized. This ensures the islanded networks to operate stably, resulting in the continuity of supply of the islanded networks, despite the absence of the main grid.